Comparison Of Human Development Index Before And During The Covid-19 Pandemic - Muammar Rinaldi; Dedeng Irawan; Armin Rahmansyah Nasution (Institute of Computer Science (IOCS), 2022)
The COVID-19 pandemic that has hit the world has brought various impacts on human life, including human development achievements. Development can be interpreted as an effort or process to make changes for the better. The development process occurs in all aspects of people's lives, such as economic, political, social and cultural aspects. The purpose of this study is to see the difference in the Human Development Index before and during the covid 19 pandemic. The research method used is the Paired Sample T-Test which is an analytical test to determine the average difference between matched data points. The results of the study show that there are differences in the Human Development Index in Indonesia, as seen from the results of the Paired Sample T-Test table. The significant value of HDI shows that there are differences in the Human Development Index in Indonesia before and during the COVID-19 pandemic. This means that the Indonesian government needs to take strategic steps and good policies to increase the human development index.